Strategic study on energy-protein requirements for local sheep: 4. Ewes during late pregnancy - I-W Mathius; D Sastradipradja; T Sutardi; A Natasasmita; L.A Sofyan; D.T.H Sihombing (Indonesian Center for Animal Research and Development (ICARD), 2002)
Thirty-six Javanese thin-tail ewes were set out to study the energy and crude protein requirements for the last eight-week of pregnancy. The ewes were randomlly assigned to a 3 x 3 factorial arrangement and offered nine diets comprising three levels of energy (low, medium and high) and three levels of crude protein (low, medium and high) with four ewes per treatment. The diets were pelleted and offered four times daily at approximately in the same amount. Results showed that, despite a difference of energy concentration in the diets, dry matter intake was not significantly (P>0.05) affected, but crude protein concentration was (P<0.05). Energy concentration in the diet also had no effect (P>0.05) on protein intake. However, protein concentration in the diets significantly affected on protein intake and protein excreted in the feces. Moreover, an interaction between energy and protein levels was not detected on energy and nitrogen availability utilization. This study demonstrated that a high efficiency on nitrogen utilization could be achieved on low crude protein diets. It was also found that crude protein and energy requirements for maintanance during pregnancy phase were 0.67 g/kg BW0.75 and 0.425 MJ EM/kg BW0.75 respectively. Key words: Protein-energy requirement, pregnancy phase, ewes